On-Line Modelling And Forecasting Of Carbon Monoxide Concentrations Using Hybird Multilayered Perceptron Network. - Raji, Usharani; Mashor, M.Y.; Ali, A.N.; Sadullah, A.F. (2005)

(untitled)
This paper discusses on-line modelling and forecasting of carbon monoxide (CO) concentrations using Hybrid Multilayered Perceptron (HMLP) Network. Th¢ HMLP network is trained using Modified Recursive Prediction Error (MRPE) algorithm.